OPTIMIZATION DESIGN OF INTERNAL GEAR PUMP BASED ON IMPROVED PARTICLE SWARM OPTIMIZATION - SUN YuanJing; QI ZhiYuan; ZHAO GuoChao (Jixie qiangdu)
In order to reduce the flow pulsation of the inner meshing gear pump,taking PGH type involute internal gear pump as the research object,the mathematical model of flow pulsation rate and tooth profile parameters was established,and the instantaneous flow rate of gear pump outer gear ring and internal gear in different meshing relations was analyzed. Based on these,a mathematical model of gear pump optimization was established. The improved particle swarm optimization was obtained by introducing the genetic operation and mutation operation of the genetic algorithm into the particle swarm optimization algorithm,through this algorithm、the parameters of gear indexing circle pressure angle、modification coefficient、addendum coefficient and tooth number were optimized,and the gear parameters of gear pump with minimum flow pulsation rate were obtained. The simulation verification was carried out by MATLAB,and the results showed that the flow pulsation rate and the tooth shape parameters of the gear pump are nonlinear; Under the condition of satisfying the structural requirements and reasonable transmission,the flow pulsation rate of the gear pump is reduced by 7. 27%,and the flow pulsation of the internal gear pump is reduced.